Modulator Dynamics Shape the Design Space for Stepwise‐Elution Simulated Moving Bed Chromatographic Separations. Issue 8 (4th June 2018) - Wayne, Chris J.; Velayudhan, Ajoy
Abstract : For proteins and other biological macromolecules, SMB chromatography is best operated non‐isocratically. However, traditional modes of non‐isocratic SMB operation generate significant mobile‐phase modulator dynamics. The mechanisms by which these modulator dynamics affect a separation's success, and thus frame the design space, have yet to be explained quantitatively. Here, the dynamics of the modulator (e.g., salts in ion exchange and hydrophobic interaction chromatography) are explicitly accounted for. This leads to the elucidation of two new design constraints, presented as dimensionless numbers, which quantify the effects of the modulator phenomena and thus predict the success of a non‐isocratic SMB separation. Consequently, these two new design constraints re‐define the SMB design space. Computational and experimental studies at the boundaries of this design space corroborate the theoretical predictions. The design of efficient and robust operating conditions through use of the new design space is also demonstrated. Abstract : Countercurrent chromatography offers greater throughput and resolution for the purification of biologics than conventional batch chromatography. Here, the Stepwise‐Elution Simulated Moving Bed Chromatography (SE‐SMB) is analyzed in detail, and present the consequences of some fundamental non‐idealities on the shape of the design space. These findings allow to design robust and efficient SE‐SMB separations for biological feedstocks.